A new look at the Earth's radiation balance from an A-train observational perspective - Henderson, David Scott, author; Stephens, Graeme L., 1952-, advisor; Heald, Colette L., committee member; Chandrasekar, V., committee member (Colorado State University. Libraries, 2010)
The weather and climate of the Earth are driven by interactions of the longwave and shortwave radiation between the Earth's atmosphere and surface. Past studies have tried to derive the Earth radiative budget through the use of models and passive satellite sensors. These past efforts did not have information about the vertical distribution of cloud or aerosols within the atmosphere that significantly influence radiative transfer within the atmosphere. This problem was improved upon with the launch of CloudSat and CALIPSO in 2006. These satellites provide the information on the vertical distribution of clouds. From CloudSat, a fluxes and heating rates product was produced to study the radiative budget, but this was limited to some degree because of undetected clouds and aerosol that have non-negligible effects on the radiative balance. This study addresses these issues by combining CALIPSO and MODIS data with CloudSat to detect and obtain the properties of cloud and aerosol undetected by the CloudSat CPR. The combined data were used to create a cloud and aerosol mask that identified distributions of undetected cloud and aerosol globally and quantified their radiative effects both seasonally and annually. Low clouds were found to have the highest impacts of nearly -6 Wm-2. High clouds globally have little effect, trapping 1 Wm-2, with the majority of the impact in the tropics. Four case studies are presented to show how heating rates change in the vertical due low cloud, cirrus, precipitation, and aerosol. The cloud and aerosol mask was used to create seasonal global distributions of cloud radiative effect using all clouds detected by CloudSat and CALIPSO, and the direct effect of aerosols estimated at the TOA. Using fluxes at the top and bottom of the atmosphere global distributions of outgoing and incoming radiation are shown, and an annual radiation budget of the Earth is derived. Clouds globally are found to have a radiative forcing of -20 Wm-2 at the TOA. The radiative budget of the Earth is calculated in two ways; using normalized shortwave fluxes by the average solar daily insolation, and by changing the solar zenith angle to simulate the diurnal cycle. Finally, the product is validated by comparing the outgoing and surface fluxes with CERES and ISCPP flux products.
Keywords: radiation; energy; CloudSat; CALIPSO; budget; A-train; Atmospheric radiation; Meteorological satellites; Terrestrial radiation